Tanzania's land law reform: The implementation challenge - Rasmus Hundsbæk Pedersen (Danish Institute for International Studies (DIIS), 2010)
A new wave of land reforms has passed Sub-Saharan African countries in recent years. Tanzania got its reform in 1999. Though expectations to outcomes are high, not much is known about how reforms affect local governance of land. This working paper provides an overview of implementation projects carried out in Mainland Tanzania and describes experiences gathered so far. It focuses on establishment of formal institutions for land administration and dispute settlement in rural areas. The implementation process is described as slow and uneven. With a few exceptions, implementation has been project-driven, largely controlled by donors and implementing agencies. At the same time the responsible ministry retains some control through its know-how, which is shared with other stakeholders in bits and pieces only. The paper concludes that more resources, more commitment and a freer flow of information is required if reform objectives are to be achieved. Independent research is urgently needed.
Keywords: 330